Annual Plan 1995-96 Volume-IV General Areas Government of Assam - Planning Commission (Planning Commission, 1995)
As in the rest of the country, during the last 40 years motorised highway transport has grown dramatically in Assam as compared to the Rail Services. Consequently it is the road system in Assam which has to bear the brunt of growing economy and population. the intensity of traffic is likely to increase further with the completion of the third bridge over river Brahmaputra in Assam.
Government of Assam, Planning and Development Department